WINGS OVER THE BALKANS (Heritage, 2022)
This research paper deals with the connections between Stanislav Krakov’s novel Wings and his memoir prose titled The Life of a Man in the Balkans. The many relations between these two works are seen through the prism of their respective themes and motifs, as well as through various genre shifts which are constantly leading the author back and forth between fiction and factography. The novelistic and real-life levels are interconnected and intertwined in a way that revitalizes the boundaries between art and the war chronicle, thus making the author ponder the questions of the meaning and the truthfulness of war events at a higher level. The tone changes in the aforementioned works, which go from skepticism, irony and sarcasm in Wings, towards sentimentality and declarative patriotism in The Life of a Man in the Balkans, demonstrate the varied reception of the novel through time.
Keywords: Anti-war novel, memoirs, avant-garde, genre, irony, sarcasm, patriotism